Analisis Kualitas Pelayanan di Puskesmas Kecamatan Kaliangkrik Kabupaten Magelang - Harda Sukma Alam; Endang Larasati; Herbasuki Nurcahyanto (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Quality of public services is the extent to which a public facility in providing services to the public. The government is required to provide quality public services. Services can be said to be good if the performance is given in accordance with the expectations required by the user community services . By using the five dimensions of service quality that is Tangible, Realibility, Responsiveness, Assurance, and Emphaty it will be able to analyze the quality of services provided by Puskemas Kecamatan Kaliangkrik Kabupaten Magelang. In this research, using a method of analysis of Importance Performance Analysis to analyze the level of satisfaction of the public by comparing the performance provided by the Puskesmas with the needs of service users.